2023
DOI: 10.3390/jfb14060299
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Exosomes in Tendon and Tendon–Bone Healing: A Systematic Review of Preclinical Studies

Abstract: Exosomes have been proven to play a positive role in tendon and tendon–bone healing. Here, we systematically review the literature to evaluate the efficacy of exosomes in tendon and tendon–bone healing. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a systematic and comprehensive review of the literature was performed on 21 January 2023. The electronic databases searched included Medline (through PubMed), Web of Science, Embase, Scopus, Cochrane Library and Ovid. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 137 publications
(1,834 reference statements)
0
6
0
Order By: Relevance
“…This could be connected to the kind of non-coding RNA of exosomes, their source, concentration, and acting time, which is an important area for future research. 31 …”
Section: Discussionmentioning
confidence: 99%
“…This could be connected to the kind of non-coding RNA of exosomes, their source, concentration, and acting time, which is an important area for future research. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Mammalian cells produce and secrete extracellular vesicles that contain a mix of proteins and nucleic acids. These vesicles are believed to play an intricate role in cell-to-cell communications [ 113 , 114 , 115 ]. The idea of using lipid bilayer membrane vesicles for the delivery of bioactive molecules to cells has been readily adopted by the drug delivery field of research [ 116 , 117 ].…”
Section: Principles Of Phage Displaymentioning
confidence: 99%
“…In the realm of tendon injury therapy, exosomes function through multiple mechanisms. These primarily include the suppression of inflammatory responses, modulation of macrophage polarization, regulation of gene expression, remodeling of the cellular microenvironment, restructuring of the extracellular matrix, and promotion of angiogenesis ( 59 ).…”
Section: Exosomes In Sports Medicine-related Researchmentioning
confidence: 99%
“…The role of exosomes in facilitating tendon-bone healing primarily encompasses (1) inhibition of inflammatory responses and regulation of macrophage polarization, (2) control of gene expression, remodeling of the cellular microenvironment, and restructuring of the extracellular matrix, and (3) promotion of angiogenesis ( 59 ). Although studies have observed the effects of BMSC-derived exosomes (BMSC-Exos) on tendon-bone healing post-ACLR in rats, both in vivo and in vitro , elucidating the possible mechanisms, it remains unclear whether BMSC-Exos can facilitate tendon-bone healing in humans post-ACLR.…”
Section: Exosomes In Sports Medicine-related Researchmentioning
confidence: 99%